Primary Renal Ewing Sarcoma in Children and Young Adults. Issue 8 (November 2020) - Bradford, Kathryn; Nobori, Alexander; Johnson, Brittany; Allen-Rhoades, Wendy; Naik-Mathuria, Bindi; Panosyan, Eduard H.; Gotesman, Moran; Lasky, Joseph; Cheng, Jerry; Ikeda, Alan; Goldstein, Jeffrey; Singh, Arun; et al.
Abstract : The Ewing sarcoma family of tumors (ESFT) are high-grade small round blue cell malignancies traditionally presenting in children and adolescents. The most common site of primary disease is bone, though extraskeletal primary sites are well-recognized. We present 6 cases of primary ESFT of the kidney and 1 case of the adrenal gland. Patients were 11 to 18 years of age at diagnosis. Metastases at diagnosis were present in most cases (n=6). All patients underwent surgery, and most received radiation (n=5). Five patients relapsed after initial remission. Comprehensive review of the primary renal ESFT literature was used to analyze various factors, including age, sex, disease metrics, metastases at diagnoses, and overall survival in a total of 362 cases. Notably, while the general ESFT population has reported rates of metastasis at diagnosis of 20% to 25%, this rate in the renal ESFT population was 53% with a rate of 59% in adolescent and young-adult patients (11 to 24 y). Nodal disease at diagnosis was present in 24% of renal ESFT cases compared with 3.2% in patients with primary skeletal ESFT. While this malignant process may share histologic and molecular features with its bone and soft tissue counterparts, primary renal ESFT presentations seem to be more aggressive and have worse outcomes. Abstract : Supplemental Digital Content is available in the text.